Pemberdayaan Start-Up dalam Program Inkubasi Bisnis di Brida Nusa Tenggara Barat - Juzri, Muh Juzri; Amir Aziz, Ahmad; Firdaus, M (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is a qualitative research with data collection methods through observation, interviews and documentation with a discussion of the BRIDA NTB business incubation program which focuses on empowering startups in West Nusa Tenggara through a holistic and integrated approach from pre-incubation to post-incubation stages. The BRIDA NTB business incubation program is a holistic and integrated initiative in empowering startups in West Nusa Tenggara (NTB). With a comprehensive approach from pre-incubation to post-incubation stages, BRIDA NTB has succeeded in creating a conducive environment for the growth and success of startup businesses in the region. In the pre-incubation stage, BRIDA NTB carries out intensive and inclusive publications through online and offline outreach activities, which increase public awareness about the opportunities that exist to participate in business incubation programs. An easy registration process and strict selection ensures quality participant participation and has the potential to grow in the local economy. During the incubation process, participants receive various forms of assistance, including training in various aspects of business, mentoring by experienced business practitioners, access to finance, intellectual property protection, and free work space facilities. Keywords : Business Incubation, BRIDA NTB, Startup